2010
DOI: 10.1007/s10549-010-0845-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk assessment in a mammography screening program and participation in the IBIS-II chemoprevention trial

Abstract: helpful to increase the participation and the understanding of chemopreventive approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 44 publications
(32 reference statements)
0
32
1
Order By: Relevance
“…We have also shown that acceptance of more intensive mammographic screening is high (81% of eligible women), and that uptake to prevention studies is relatively low (17%-20%) in the women we identified as high risk. Nevertheless, uptake to PROCAS and to the preventive interventions offered was considerably greater than in a recent study on risk assessment in a population setting from Germany (44) in which 17.7% (n ¼ 446) of participants met the eligibility criteria for IBIS-II, but only 202 of 445 (45%) wished to be informed of their breast cancer risk and only 0.7% (3/446) eventually entered IBIS-II.…”
Section: Discussionmentioning
confidence: 70%
“…We have also shown that acceptance of more intensive mammographic screening is high (81% of eligible women), and that uptake to prevention studies is relatively low (17%-20%) in the women we identified as high risk. Nevertheless, uptake to PROCAS and to the preventive interventions offered was considerably greater than in a recent study on risk assessment in a population setting from Germany (44) in which 17.7% (n ¼ 446) of participants met the eligibility criteria for IBIS-II, but only 202 of 445 (45%) wished to be informed of their breast cancer risk and only 0.7% (3/446) eventually entered IBIS-II.…”
Section: Discussionmentioning
confidence: 70%
“…This might be because of the study design. Earlier studies by our group have shown that awareness of breast cancer risk leads to greater willingness among women to address their own risk of breast cancer, either by obtaining information about the risk or by taking part in chemoprevention studies (Fasching et al, 2007;Loehberg et al, 2010). Inviting healthy control individuals to take part in a case-control study for breast cancer might have led to a bias of this type.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally incorporating cross-over trial designs where all subjects will have the opportunity to receive study agent and placebo may be a more acceptable option. Emphasizing the importance of trial requirements thorough counseling at study presentation has been observed to improve recruitment of better research team and subject dynamics [14,25,26]. …”
Section: Discussionmentioning
confidence: 99%